The South Korean Perspective on German Animal Welfare Certified Pork - Rebecca Derstappen; Annika Johanna Thies (German Journal of Agricultural Economics (GJAE), 2024)
Industry stakeholder requests for improved animal welfare practices in German meat production have steadily increased in recent years. A transformation of German animal husbandry systems would almost certainly result in higher production costs. Against this background, producers and the meat industry are concerned about losing their international competitiveness while implementing improved animal welfare practices. As South Korea is an established trading partner for Germany, the objective of this explorative study is to assess South Korean meat market trends with a special focus on meat quality and animal welfare in order to evaluate export chances for German pork produced under higher animal welfare standards. Using a triangulation, the results of semi-structured interviews (n=15) with South Korean pork supply chain stakeholders are combined with the results of an online survey of South Korean consumers (n=723). Results indicate that the market potential for German meat produced under higher animal standards is still low in South Korea. Stakeholders associate improved husbandry conditions with healthier animals, benefits to human health and rank animal welfare as a key element of sustainability. However, due to consumers' lack of knowledge and their price sensitivity, animal welfare is neither a unique selling point, nor linked to meat quality.
Keywords: 330; South Korea; Animal Welfare; Meat Quality; German Pork; Export